Doing business with Kazakhstan : a guide to investment opportunities & business practice. (Global market briefings., 2004)
This third edition of Doing Business with Kazakhstan provides invaluable, authoritative and practical advice on the business and investment environment in Kazakhstan. The country has vast natural resources and one of the world's largest oil, gas and mineral deposits.